THE PSYCHOLOGICAL HELP DURING EXPERIENCING OF LOSS - CAN WE HELP PEOPLE TO EXPERIENCE THEIR GRIEF? - Rybyk, Larisa (PSYCHOLOGICAL JOURNAL, 2018)
The headnotegives reasonsfor the research actuality of problem of loss and grief experiencing, including perished law enforcement officers` wives in Ukraine, providing them with psychological advising and necessary psychological help on the basis of modern scientific heritage, world and local practical experience. Common factors of the psychical and physical personality functioning are considered while experiencing ofsignificant person death. The special attention was attended to the researches that studied influence of significant person sudden death on the futurelife. Scientists contend that an unexpected deathin particularis one of principal reasons of development of pathological reactions of experiencing grief that in modern scientific literature is also known as difficult grief, traumatic grief, prolongedmourning disorder. These disorders are related to functional violations, declining living standards, and with the increase of diseases level, both psychical (depression, anxiety, deadaptationetc.) and somatic ones. Researches of persistent complex disorders of the members of the perished servicemen`s families, conducted by the American scientists, confirm that the circumstances of death and relation in family have an influence on intensity of grief experiencing. The researches examiningsocio-economic factors influence on grief experiencing are presented. Not only in the countries of the third world but also in the developed European countriesthe social position, a low level of education and belonging to women sex are factors influencing on forming of complicated grief. The research aimsare study of psychotherapy features at grief experiencing on the basis of researches of scientists from different countries of the world and the parallel analysis, what factors psychotherapy influences on and whether it is effective. The basic part reviewed the basic theoretical and practical approaches to the near determination of psychological help. A social help is considered as first one, most natural and accessible. It can provide a buffer effect and prevent stress factors influence on other spheres of life. However,it is necessary to take into account that significant person`s death brings both to social and to emotional loneliness. Social support diminishes the level of social loneliness, but can not influence on emotional one, which is essential in grief experiencing. Professional, psychological help efficiency was also examined on an analysis of earlier studies. Now in scientific society a discussionis actively conducted, concerning psychological help influence on the process of grief experiencing. Some scientists came to the conclusions, that there are no confirmations of positive results of psychotherapy. Furthermore, it is considered that psychological interference can influence on the dynamics of normal grief. However, practically all scientists agree, that psychological help is necessarywhile experiencing of the complicated grief. It is also specified on that pathological reactions can be avoided withthe systematic psychological accompaniment.There are some contradictions that suggest an idea about positive influence of psychological accompaniment. The researches conducted in England, Germany, Turkey, Ukraine indicate positive dynamics of influence of the programs of psychological help. In a conclusion practicability of synthesis of social support and psychological help at significant person death is stated.